'It's in my blood now': the satisfaction of rangers working in Queen Elizabeth National Park, Uganda. Issue 4 (21st June 2016) - Moreto, William D.; Lemieux, Andrew M.; Nobles, Matt R.
Abstract: Investigating the human dimension of conservation science warrants an interdisciplinary approach. Criminologists and criminal justice scholars have begun to empirically examine various issues that are directly related to conservation, including wildlife law enforcement. This qualitative study of job satisfaction among law enforcement rangers in a protected area in Uganda contributes to both criminal justice and conservation science. Based on interviews and participant observation we identified four main themes that contributed positively to the job satisfaction of rangers: their role in aiding Uganda's conservation efforts and national development; financial stability and familial support; conducting frontline work and establishing ownership of the Park; and opportunities for personal and social development. We discuss the implications of our findings for Park management capacity building as well as for future interdisciplinary and qualitative scholarship in conservation science.